2020
DOI: 10.1590/s2179-975x3219
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta diversities of Trichoptera (Insecta) assemblages in natural and rural subtropical streams

Abstract: Aim The aim of this study was to determine the diversity of Trichoptera in subtropical streams and the effects of environmental variables and geographical position on alpha and beta diversity in natural and rural streams. Methods We collected Trichoptera with a Surber sampler in 12 small order subtropical streams (six streams with apparent absence of anthropic disturbance and six streams with rural activity in their drainage areas) and measured limnological variables. We evaluated the effects of environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Studies demonstrate that changes in areas adjacent to streams can cause chemical changes in the water (for example, through the transport of sediments or chemicals) favoring the dominance of tolerant organisms (Hepp et al, 2010;Huiñocana et al, 2020;Hepp et al, 2021). Among the Trichoptera genera, Smicridea and Itaura are widely observed in streams with agricultural use (Breda et al, 2020), while Caenis has been reported as an Ephemeroptera genus tolerant to anthropogenic disturbances (Arimoro & Muller, 2010). In addition, our results clearly demonstrated the effects of organism abundance on richness.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Studies demonstrate that changes in areas adjacent to streams can cause chemical changes in the water (for example, through the transport of sediments or chemicals) favoring the dominance of tolerant organisms (Hepp et al, 2010;Huiñocana et al, 2020;Hepp et al, 2021). Among the Trichoptera genera, Smicridea and Itaura are widely observed in streams with agricultural use (Breda et al, 2020), while Caenis has been reported as an Ephemeroptera genus tolerant to anthropogenic disturbances (Arimoro & Muller, 2010). In addition, our results clearly demonstrated the effects of organism abundance on richness.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, we can see that changes in streams adjacent areas (e.g., land use) are important environmental predictors in the structuring of aquatic insect communities. Thus, it is expected that changes in land use in the stream drainage area will affect the limnological water quality and, consequently, the aquatic biota (Breda et al, 2020;Castro et al, 2021). In this study, we observed that the vegetation removal was decisive for the change in limnological variables such as water temperature, pH, and dissolved oxygen.…”
Section: Discussionmentioning
confidence: 62%